Sustaining community-based interventions for people affected by dementia long term: the SCI-Dem realist review. Issue 7 (7th July 2021) - Morton, Thomas; Wong, Geoff; Atkinson, Teresa; Brooker, Dawn
Abstract : Objectives: Community-based support for people with earlier-stage dementia and their care partners, such as regularly meeting groups and activities, can play an important part in postdiagnostic care. Typically delivered piecemeal in the UK, by a variety of agencies with inconsistent funding, provision is fragmented and many such interventions struggle to continue after only a short start-up period. This realist review investigates what can promote or hinder such interventions in being able to sustain long term. Methods: Key sources of evidence were gathered using formal searches of electronic databases and grey literature, together with informal search methods such as citation tracking. No restrictions were made on article type or study design; only data pertaining to regularly meeting, ongoing, community-based interventions were included. Data were extracted, assessed, organised and synthesised and a realist logic of analysis applied to trace context–mechanism–outcome configurations as part an overall programme theory. Consultation with stakeholders, involved with a variety of such interventions, informed this process throughout. Results: Ability to continually get and keep members; staff and volunteers; the support of other services and organisations; and funding/income were found to be critical, with multiple mechanisms feeding into these suboutcomes, sensitive to context. These included an emphasis on socialising and person-centredness; lowering stigma and logistical barriers; providing support and recognition for personnel; networking, raising awareness and sharing with other organisations, while avoiding conflict; and skilled financial planning and management. Conclusions: This review presents a theoretical model of what is involved in the long-term sustainability of community-based interventions. Alongside the need for longer-term funding and skilled financial management, key factors include the need for stigma-free, person-centred provision, sensitive to members' diversity and social needs, as well as the need for a robust support network including the local community, health and care services. Challenges were especially acute for small scale and rural groups.